The pandemic and HEIC structural challenges: SUS funding, the federalized health services, and public-private relations - Dweck, Esther; Moretti, Bruno; Cardoso de Melo, Maria Fernanda Godoy (Cadernos do Desenvolvimento, 2023)
This article aims to demonstrate how structural fragilities of the Economic and Industrial Complex of Health (HEIC) associated with Brazilian public finances have manifested during the novel coronavirus pandemic, requiring emergency responses. The paper discusses in particular: a) the fiscal rules’ impacts on the Unified Health System (SUS) funding; b) the asymmetrical design of the Brazilian fiscal federalism between services delivered by subnational entities and their dependence on the federal government; c) public-private partnerships and their effects on HEIC, especially those involving the inequity on the access to hospital beds, the regulation of health insurances regarding the pandemic, and the norms for the purchase of strategic products given Brazil’s external dependence. To conclude, an agenda must be set to respond to the structural challenges of SUS and the vulnerabilities of HEIC in a context of increasing demand for health services and technological changes.